Determinants of individual tax return filing compliance: Evidence from Indonesian civil servant teachers using PLS-SEM - Br. Sembiring, Ceria Angellita Atengena; Sitompul, Grace Orlyn; Sinaga, Judith Tagal Gallena (Trigin Publisher, 2026)
This study investigates the determinants of individual taxpayer compliance in filing annual tax returns among Indonesian civil servant teachers. The population of this study consists of civil servant public senior high school teachers in Pasuruan Regency, with a total population of 190 teachers. The number of samples collected was 68 respondents. Previous studies have reported inconsistent findings regarding the effectiveness of tax information dissemination and digital tax system integration in improving compliance behavior. This study aims to examine the role of tax information dissemination, tax interpretation, and tax information system integration in influencing taxpayer compliance. A quantitative research design was used with a survey approach. This study contributes to the tax compliance literature by emphasizing the importance of taxpayer understanding and digital system integration in improving compliance behavior among civil servant taxpayers.